Integrating health-related factors in the technological acceptance model for predicting health-related Internet use - Ahadzadeh, Ashraf Sadat (2014)
Today, people use the Internet to satisfy health-related information and communication needs. Women are dominant Internet users in terms of health purposes. In Malaysia, Internet use for health management has become increasingly significant due to the increase in the incidence of chronic diseases, in particular among urban women, and their desire to stay healthy. Past studies adopted technology acceptance model (TAM) and health belief model (HBM) independently to explain Internet use for health-related purposes. TAM explains technology-related factors for Internet use whereas HBM purely explains health-related Internet use from a health perspective. While both TAM and HBM have their own merits, independently they lack the ability to explain the cognition and the related mechanisms in which individuals use Internet for health purpose. The main objective of this study is to develop an integrated model of health-related Internet use based on the health belief model (HBM) and the technology acceptance model (TAM). This study specifically aims to examine the influence of perceived health risk and health consciousness on health-related Internet use based on the HBM. Drawing upon the TAM it also tests the mediating effects of perceived usefulness of Internet for health information and attitude towards Internet for health purposes on the relationship between health-related factors, namely perceive health risk and health consciousness, and health-related Internet use. Data obtained for the current study were collected using proportionate sampling and the sample consisted of non-academic female staffs working at the Universiti Putra Malaysia (UPM). A total of 293 respondents were selected for this study and Partial Least Squares-Structural Equation Modeling was used to test the research hypotheses developed for this study. The results of this study revealed that perceived health risk and health consciousness have a positive influence on health-related Internet use. Additionally, perceived usefulness of Internet was influenced by perceived health risk and health consciousness. Perceived ease of Internet use and perceived usefulness also showed the positive impact on attitude towards the Internet use for health information which in turn had a positive effect on health-related Internet use. Moreover, perceived usefulness of Internet and attitude towards the Internet use for health-related purposes partially mediated the influence of health consciousness on health-related Internet use while the effect of perceived health risk on health-related Internet use was fully mediated by perceived usefulness of Internet and attitude. These results suggested the central role of perceived usefulness of and attitude towards Internet for health purpose for women who were health conscious and who perceived their health to be at risk. The integrated model proposed and tested in this study shows that HBM when combined with TAM is able to predict the Internet use for health purpose. For women who subjectively evaluate their health as vulnerable to diseases and are concerned about their health, cognition beliefs in and positive affective feelings about Internet come into play in the use of Internet for health-related purposes. Furthermore, engaging in health-related Internet use is a proactive behavior rather than a reactive behavior, suggesting the significant mediating role of the TAM dimensions in using the Internet for health management.